ANALISIS PENGARUH PENAMBAHAN AGREGAT LIMBAH PLASTIK (POLYETHYLENE TEREPHATHALATE) TERHADAP KUAT TEKAN BETON - Masril Masril; Jefry Rizaldo (Ensiklopedia of Journal, 2021)
Plastic Material Plastic waste is a problem that is very often encountered in urban and rural areas. The use of plastic in each year will continue to increase because food and beverage products all use materials made of plastic. However, the plastic in question is plastic that is difficult to contaminate with soil or commonly referred to as inorganic waste, which is difficult to self-destruct. This is what causes the amount of plastic waste to increase.Therefore, to reduce this waste, the volume of this waste is used in the development. Besides, the grain gradation of the aggregate has been determined with the aim of obtaining an increase in the compressive strength of the concrete with the addition of plastic waste. The quality of the concrete to be examined by the authors in this study is fc = 14.5 MPa. In other words, in this study the author tries to compare the compressive strength of concrete between normal concrete and concrete mixed with plastic waste. In this study also used a variation of plastic waste substitution with a ratio of 0%, 5%, 10% to the volume of fine aggregate. For each variation, 2 samples were used which included normal concrete so that the total test object used was 12 tested at 7 days, 14 days and 28 days of concrete.From the results of testing the compressive strength of concrete against normal concrete and mixed concrete with sawdust surian at the age of 28 days, the normal concrete compressive strength is 14.5 MPa, while in the sawdust mixture with a percentage of 5%, the concrete compressive strength is 14.14 MPa. 10% obtained a compressive strength of 17.05 MPa. From this test, it can be concluded that from each of the percentages that are made, the compressive strength increases along with the percentage of the amount of plastic waste added to the concrete mixture. In other words, the greater the percentage of plastic waste used, the higher the compressive strength and quality of the concrete produced.